A Structural Model of Well-being: with an application to German Data - Bernard M.S. van Praag; P. Frijters; A. Ferrer-i-Carbonell (Tinbergen Institute, 2000)
In this paper we attempt to explain individual, ordinally comparable,satisfaction levels. We postulate a simultaneous equation model where general satisfaction isexplained by exogenous shock and level variables, and by the values of the satisfactionswith respect to six distinct endogenous domains of life. Taking into account that thesesatisfactions were categoricallymeasured and allowing for individual effects, the model was estimatedon six consecutive waves of the German Socio-Economic Panel. The results are statistically verysignificant and plausible.The main conclusions of this paper are:given the fact thatwe get stable significant andintuitively interpretable results, the assumption of interpersonal(ordinal) comparability ofsatisfactions cannot be rejected on the grounds that it leads toinsignificant or implausible results;It is possible to explain satisfactions to a large extent byobjectively measurable variables;Domain Satisfactions are strongly interrelated because of commonexplanatory variables;General Satisfaction may be seen as an aggregate of the six domainsatisfactions.
Keywords: 330; Lebensqualität; Sozialer Indikator; Theorie; Deutschland